(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Open and online education can be effectively applied to „Special target groups‟ in both the undergraduate and postgraduate segments. Amongst other resources, these target groups require tailored, flexible education formats, individual learning pathways, more accessible, lifelong learning programmes and the opportunity to keep abreast of rapidly developing fields. Under this segment various target groups like Persons with Disability, Transgender, Defence and Paramilitary forces, Prison inmates, Orphanage inmates, Old age home inmates, widowers etc. Those individuals who don‟t have equal access to the education in regular mode compared to the other students, are facilitated to continue their studies through Online Education. Special features of Online education are the students can study in their convenient time with their own pace of learning, content availability and assessment would be online which facilitate them to continue their education without hurdles. The current study focuses on the measures to reach out the Special Target Groups in Online Education.